Mosquito Trap In The Laboratory Of FMIPA UNY'S Biological Garden To Reduce Mosquito Disorders - Saputra, Dian; Rahmawati, Fauziah; Nisa, Devia Khoirun; Putri, Astried Hanggana (Jurnal Pengabdian Masyarakat MIPA dan Pendidikan MIPA, 2019)
Mosquitoes are animals that are very often found in everyday life. Starting from the home environment, to the school environment. Mosquitoes are also animals that can carry various diseases. The FMIPA UNY Biology Garden Laboratory is overgrown with trees and there is a pool of water from several ponds that are deliberately made. That is what makes mosquitoes like the environment that is included in their habitat. At the UNY Biology Garden Laboratory, which is one of the student learning locations, mosquitoes are found flying and sometimes disrupting learning activities because they can stab and cause itching. The disturbance is feared to cause mosquito-borne diseases in students who are active in biology gardens. So that mosquito traps are made that are modified and adapted to the needs and location of the target. The tool made is a simple mosquito trap that utilizes a pool of water from a fish pond and a net from mesh or paranet cloth. The target place is the FMIPA UNY Biology Garden Laboratory, especially the pool area. While the target is the larvae or seeds of mosquitoes left by the mother. It is expected that the mosquitoes will perch on the paranet to lay eggs, then the eggs will fall down and will be eaten by fish. This is in addition to reducing the growth of mosquitoes, it can also be used for alternative food for fish, which can reduce spending to buy fish feed. Key words: mosquitos, trap